Coping Strategies and Religiosity as Predictors of Mental Well-Being Among Israeli-Palestinian Teachers - Egbaria, Hamza (European Scientific Journal, ESJ, 2026)
This cross-sectional study examined whether coping strategies and religiosity predict mental well-being among Israeli-Palestinian teachers. Using a convenience sampling technique, data were collected from 415 Israeli-Palestinian teachers who completed an anonymous online survey including the Warwick–Edinburgh Mental Well-Being Scale, the Brief-COPE, and the Arab Scale for Religiosity. Descriptive findings showed moderate to high levels of problem-focused and emotion-focused coping, lower levels of avoidant coping, and generally high levels of mental well-being and religiosity. Correlation analyses indicated small positive associations between mental well-being and both problem-focused and emotion-focused coping, whereas religiosity showed a strong positive association with mental well-being. Multiple regression analysis revealed a significant overall model explaining 9.1% of the variance in mental well-being. Religiosity emerged as a significant, unique predictor, while coping styles and demographic variables showed relatively small effects. The findings suggest that religiosity may serve as an important protective resource for teachers’ mental well-being, whereas coping contributes in expected but more modest ways. The study highlights the value of culturally responsive approaches to supporting teacher well-being in the Arab educational context in Israel.